2009
DOI: 10.5194/angeo-27-2371-2009
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of equatorial F-region plasma depletions over Brazil during the Spread-F Experiment (SpreadFEx)

Abstract: Abstract. From September to November 2005, the NASA Living with a Star program supported the Spread-F Experiment campaign (SpreadFEx) in Brazil to study the effects of convectively generated gravity waves on the ionosphere and their role in seeding Rayleigh-Taylor instabilities, and associated equatorial plasma bubbles. Several US and Brazilian institutes deployed a broad range of instruments (all-sky imagers, digisondes, photometers, meteor/VHF radars, GPS receivers) covering a large area of Brazil. The campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
4
17
3
Order By: Relevance
“…These characteristics are typical of previous bubble measurements over Brazil (e.g. Taylor et al, 1997b;Pimenta et al, 2003;Arruda et al, 2006), and separate investigations comparing the scale-sizes of the mesospheric gravity waves and F-region depletions, and the longitudinal variability in the bubble characteristics are presented by Takahashi et al (2009);Pautet et al (2009).…”
Section: Coordinated Observationssupporting
confidence: 57%
See 1 more Smart Citation
“…These characteristics are typical of previous bubble measurements over Brazil (e.g. Taylor et al, 1997b;Pimenta et al, 2003;Arruda et al, 2006), and separate investigations comparing the scale-sizes of the mesospheric gravity waves and F-region depletions, and the longitudinal variability in the bubble characteristics are presented by Takahashi et al (2009);Pautet et al (2009).…”
Section: Coordinated Observationssupporting
confidence: 57%
“…For the SpreadFEx campaign three high-quality imaging systems were used to quantify the occurrence and properties of mesospheric gravity waves and F-region depletions over Brazil using coordinated observations of several mesospheric and thermospheric nightglow emissions (see Pautet et al, 2009;Vargas et al, 2009;Wrasse et al, 2009). In particular, all-sky (180 • field of view) image measurements provide two-dimensional information with high spatial and temporal resolutions over a large geographic area (e.g.…”
Section: Imaging Instrumentationmentioning
confidence: 99%
“…The climatology and characteristics of low-latitude F-region plasma drift have been extensively studied over the past few decades using ground-based radar observations, optical measurements, ionosonde, and satellite observations [1,2,3,4,5,6,7,8]. The previous studies have shown that the night-time zonal plasma drifts in geomagnetically quiet days were eastward while plasma drift during the geomagnetic disturbance days are westward.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is the same as applied to analyzing wave motions in mesospheric image data [e.g., Taylor and Garcia , 1995; Garcia et al , 1997]. The method used to measure the zonal velocity of the plasma bubble is similar to that proposed by Pimenta et al [2001] and employed by Pautet et al [2009] and Chapagain et al [2011] to quantify bubble drift speeds over equatorial Brazil and Christmas Island, respectively. In each case, the velocities of individual bubbles were estimated using the embedded depletion structures visible from pairs of consecutive OI (630.0 nm) images separated in time by ∼12 min.…”
Section: Observations and Data Analysismentioning
confidence: 99%